Experience with Grapevine: The Growth of a Distributed System - Schroeder, Mike; Birrell, Andrew; Needham, Roger (ACM Transactions on Computer Systems, 1984)
Grapevine is a distributed, replicated system that provides message delivery, naming, authentication, resource location, and access control services in an internet of computers. The system, described in a previous paper [1], was designed and implemented several years ago. We now have had operational experience with the system under substantial load. In this paper we report on what we have learned from using Grapevine.